A contrastive analysis of morphological and syntactic aspects of English and Indonesian adjectives - Luthfi Auni; Abdul Manan (Studies in English Language and Education, 2023)
This study’s main focus was describing adjectives’ characteristics in English and Indonesian. It examined the similarities and differences in the features of adjectives in the two languages through a parallel comparison using the contrastive analysis approach. Data were collected from linguistics books from both languages. The results indicated that similarities and differences are found almost in all aspects of adjectives in both languages when analysed from the viewpoint of their classifications according to their forms, formations, meanings, and positions. At the morphological level, the reduplication form found and shared in Indonesian is not found in English. The habits of using Indonesian reduplication adjectives, which denote something done repeatedly and used for emphasis, tend to make Indonesian learners apply this rule to English. Both languages use different systems in terms of affixation as the formation of adjectives. English adjectives only have two kinds of affixes, namely prefix and suffix, while Indonesian ones have four kinds of affixes such as prefix, infix, confix, and suffix. The differences between native and foreign languages in forms, formations, meanings, and positions cause learning and teaching process difficulties. By knowing and understanding similarities and especially differences, teachers and students can solve the problems of learning and teaching English adjectives since these differences are the fundamental aspects of the problems faced by Indonesian native speakers when studying the target language. Consequently, having a good understanding of this critical aspect of the English language can reduce problems of learning and teaching English to Indonesian native speakers.